Salivary steroid hormone responses to dyadic table tennis competitions among Hong Kongese juvenile boys. Issue 6 (2nd November 2018) - McHale, Timothy S.; Gray, Peter B.; Chan, Ka‐chun; Zava, David T.; Chee, Wai‐chi
Abstract: Objectives: Little is known about salivary steroid hormone responses to dyadic competition among prepubescent boys. The current study explored pre‐match and post‐match testosterone, dehydroepiandrosterone (DHEA), androstenedione, and cortisol among 22 ethnically Chinese, Hong Kongese table tennis athletes, aged 8‐11 years, during dyadic competition against peers. These data provide novel comparative insight into boys' hormone responses when participating in similar forms of competition to that of adults. Methods: Measures of salivary steroid hormones, age, outcome, and participant's self‐reported perceived performance were obtained. Pre‐match salivary steroid hormones and competition‐induced steroid hormone changes were explored to further assess overall hypothalamic‐pituitary‐adrenal axis activity. Results: Cortisol decreased for most participants, whereas testosterone measures were below the sensitivity of the assay. DHEA and androstenedione did not significantly change during the table tennis exhibitions and were unrelated to independent performance variables. Correlational analyses indicated that competition‐induced androstenedione and cortisol change were positively related. Conclusions: Findings show that juvenile boys' steroid hormone responses during dyadic athletic competition differ in comparison to adult males, in whom cortisol and testosterone tend to rise. Lack of significant DHEA and androstenedione change during the table tennis competition differs from our previous work that showed DHEA and androstenedione were sensitive to more physically taxing forms of athletic competition (eg, soccer). These results are discussed in light of potential factors that may have contributed to these differences.